Inducement of Agarwood Resin Using Various Chemical Formulation of Stem Tissue (Aquilaria malaccensis) - Husni Ibrahim (Journal of Global Pharma Technology, 2019)
Agarwood is described as fragrance wood that is usually derived from the trunk of genus Aquilaria which have been infected by a particular disease. The main focus of this research is to study the effectiveness of four chemical inoculants applied into 6 year old karas tree (A. malaccensis) plantations in Slim River, Perak, Malaysia using dripping techniques. The inoculants used were labelled as A, B, C and D. Commercial inoculant, labelled as K, was used for comparison purposes and control labelled as N. After eight months of inoculation, the karas tree were cut down and discoloured tissue samples were collected.  Solvent extraction methods using dichloromethane (DCM) was carried out to obtain the resin crude extract from the plant tissue. Resin crude extract were then analysed using gas chromatography-mass spectrometry (GC-MS). The results showed that all chemicals successfully stimulated agarwood production. Inoculant A produced the highest crude extract recovery (8.63%) compared to inoculants B (7.45%), D (6.55%), C (5.95%), K (1.89%) and N (0.49%). GC-MS analysis revealed that aromatic compounds, sesquiterpenes, monoterpenes, sterols, alkanes and fatty acid methyl ester were identified from DCM extract. As an outcome, inoculant A is the best to be used as stimulant for agarwood due to product highest yield. This finding will hopefully contribute to new types of inoculants production in agarwood industries in Malaysia.Keywords: Agar wood, artificial inoculation, Chemical inducement, Aquilaria malaccensis, Malaysia